Salivary gland function in women with Hashimoto’s thyroiditis without xerostomia and the correlation with auto-thyroid antibodies - Pang, Xiao-an; Wei, Zhi-xiao; Li, Jun-hong; Pang, Xiao-qi (Nuklearmedizin - NuclearMedicine, 2020)
Background Hashimoto’s thyroiditis (HT) may cause salivary dysfunction in patients resulting in xerostomia, but little is known about changes in salivary function in patients with no obvious dry mouth symptoms. In this study we assessed salivary function in women with HT, who had not experienced xerostomia and, for the first time, evaluated the effects of thyroid auto-antibodies on this function.Methods Sixty consecutive subjects were included, comprising 32 women (mean age, 36 ± 12 years) diagnosed with HT accompanied by differentiated thyroid cancer (DTC) in the study group (HT group), along with a control group (DTC group) of 28 women (mean age, 40 ± 12 years) diagnosed with DTC only. Salivary gland scintigraphy was used to assess salivary function with the semi-quantitative parameters of maximum absorption ratio and maximum secretion ratio, the decrease of which indicate impaired salivary function. Moreover, the HT and DTC groups were divided into four subgroups (Anti– HT, Anti+ HT, Anti– DTC, and Anti+ DTC), based on the presence of anti-thyroid peroxidase antibody (TPOAb) and anti-thyroglobulin antibody (TgAb). Finally, salivary gland semi-quantitative parameters were correlated with levels of thyroid-stimulating hormone (TSH), TGAb, and TPOAb in the HT and DTC groups.Results None of the semi-quantitative parameters examined in parotid or submandibular glands differed significantly between the HT and DTC groups. However, the maximum secretion ratio for the parotid and submandibular glands were significantly different in the subgroup comparison (p < 0.05). Furthermore, the TgAb, TPOAb, and TSH values correlated significantly with salivary excretive function (p ≤ 0.05).Conclusion Women with HT without xerostomia may not have salivary functional impairment during hypothyroidism. Serum thyroid autoantibody and TSH levels may mainly influence salivary excretive function but not uptake function.
Keywords: Speicheldrüse; Speicheldrüsen-Szintigraphie; Hashimoto-Thyreoiditis; Schilddrüsen-Autoantikörper